Linguistic Analysis Of Surah Makkiyah And Madaniyah From The Ilmu Ma'ani Perspective/ Linguistic Analysis Of Surah Makkiyah And Madaniyah From The Ilmu Ma'ani Perspective - Cahyono, Ismawan Dwi; Febriyanti, Putri (Bumi Lingua Edu Center, 2024)
Ilmu Ma'ani studies how to convey Arabic sentences according to the situation and conditions. This article discusses the linguistic characteristics of surah Makkiyah and Madaniyah in the Qur'an from the perspective of ma'ani studies. The method used is the analysis of the Arabic text of the Qur'an, surah Makkiyah and Madaniyah. The results: surah Makkiyah show a strong and effective language style to convey the main message about monotheism, the last day, and threats to those who deny the truth; by using kalam khabari to emphasize the truth of revelation and kalam insha'i, such as: Commands (amr) and rhetorical questions (istifham) that arouse the thoughts and feelings of the reader. Surah Madaniyah emphasize the social and legal aspects of Islam. The diversity of the use of kalam insha'i, including commands (amr), calls (nida'), rejections (nafi), and oaths (qasm), provides practical guidance for Muslims and strengthens the instillation of moral and social values. This study shows that the differences in language style are in accordance with the historical context and needs of society when the Quran was revealed, and reinforce the message conveyed in the holy book.